Typical and Atypical Processing of Gaze (Frontiers Media SA, 2021)
The eyes represent an important social cue and they typically play key roles within key part of typical non-verbal communication. When people view the faces of other people, they typically spend the most time looking at the eyes compared to other features of the face. Attending to the eyes facilitates social interactions because they can be used to indicate interest by someone else, and during conversations the eyes help to indicate turn-taking or disapproval etc. Since people tend to gaze in the direction of items in their environment that they are most interested in, perceiving the direction and target of others’ gaze can help inform about the focus of people's current mental and emotional state, including their interests, beliefs and desires. The gaze of others is so powerful that when people shift their attention, this also tends to shift observers' own attention in the same direction. This effect happens even when we know that the shift of attention by someone else is not informative, or is even misleading. Gaze also helps us to interpret other types of social signals in others. For example, different directions of gaze help to facilitate specific emotional expressions that are linked to those gaze directions, over the processing of other emotions. Our understanding about the normal mechanisms underlying the processing of gaze has also been informed by research and theory involving people with disorders involving differences in gaze processing, such as autism spectrum disorders (ASD). There are commonly reported difficulties in reading mental states from the eyes of others in ASD, which are associated with differences in brain activity in regions associated with the processing of gaze. However, while people with ASD have difficulties reading mental states from the eyes, they often show typical effects of reflexive gaze from the gaze shifts of others. Unfortunately, little is currently known about the underlying mechanisms for the pattern of intact and atypical processing of gaze in ASD at cognitive and neural levels. There is currently a need for further theoretical development and understanding at both the cognitive and neural level of functioning. While there are regions of the brain associated with gaze processing, how the neurons in these different regions exactly code for different gaze directions is still not well known, nor how we integrate cues from different aspects of the eyes, head and context to perceive the gaze of others. Similarly, little is known about inhibiting gaze information when it is task irrelevant, or is even detrimental for performance. The aim of this Research Topic collects articles on different types of methodologies and on the processing of gaze. This includes the effects of others' gaze on our cognitive, behavioural and neural processes, and the use of gaze in understanding other people etc.